2015
DOI: 10.1111/1747-0080.12205
|View full text |Cite
|
Sign up to set email alerts
|

Are dietetics educators' attitudes to assessment a barrier to expanding placement opportunities? Results of a Delphi study

Abstract: Aim: Assessment of entry-level health professionals is complex, especially in the work-based setting, placing additional pressures on these learning environments. The present study aims to gain understanding and ideally consensus regarding the setting for assessment of all elements of competence for entry-level dietitians across Australia. Methods: Seventy-five experienced academic and practitioner assessors were invited to participate in an online Delphi survey. The 166 entry-level performance criteria of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%